Benzotriazole based polymers with different side chains employed as dopant-free hole-transporting materials for high-efficiency perovskite solar cells. Issue 46 (22nd November 2022) - Yao, Lu; You, Guofeng; Wang, Xuelin; He, Zhichao; Zhou, Zhonggao; Li, Kan; Zhen, Hongyu; Ling, Qidan
Abstract : Two benzotriazole based polymers with different side chains are developed as dopant-free hole-transporting materials for n–i–p perovskite solar cells. PBTA-26 bearing ethylhexyl side chains endow the device with an efficiency of 19.83%. Abstract : Donor (D)–electron acceptor (A) conjugated polymers are promising dopant-free, hole-transporting materials (HTMs) for perovskite solar cells (PVSCs) due to their tunable energy levels and band gaps, high hole mobility, and good film morphology. Owing to the superior carrier transport properties and multiple functional sites, benzotriazole (BTA) is a popular A unit to construct D–A polymeric donors for organic solar cells. By comparison, BTA based polymers employed as polymeric HTMs are studied much less. Herein, BTA units with different side chains are studied as the A unit of two polymeric HTMs, in which benzo[1, 2 b :4, 5 b ′] dithiophene (BDT) served as the D unit. BTA bearing the branch side chains of ethylhexyl endows BDT-BTA copolymer PBTA-26 with higher hole mobility and better film morphology than PBTA-8 with the straight side chains of octyl. The n–i–p PVSCs employing PBTA-26 as a dopant-free HTM exhibited a power conversion efficiency of 19.83%, which is thought to be among the highest performances achieved from the PVSCs with BTA based HTMs. This work will enrich the variety of high-performance polymeric HTMs.